A Modified Analytic Function Space Feynman Integral and Its Applications. (20th July 2014) - Chang, Seung Jun; Choi, Jae Gil; Chung, Hyun Soo
Abstract : We analyze the generalized analytic function space Feynman integral and then defined a modified generalized analytic function space Feynman integral to explain the physical circumstances. Integration formulas involving the modified generalized analytic function space Feynman integral are established which can be applied to several classes of functionals.